IMPLEMENTASI KEBIJAKAN REVITALISASI POSYANDU DI PUSKESMAS KAWAT KECAMATAN TAYAN HILIR KABUPATEN SANGGAU - Lusilia E.42008013 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
The title of this research is "The Implementation of The Revitalization Policy of Posyandu at Puskesmas Kawatin the district of Tayan Hilir, Region of Sanggau. This thesis research aims to describe the activity of TheRevitalization of Posyandu at Puskesmas Kawat and to describe the factors that affect that activity. The title ofthis thesis raised based on the problem of the implementation of the revitalization policy at Puskesmas Kawatwhich has not implemented optimally. This research uses a qualitative analysis with three phases of analysis:data reduction, data presentation and conclusion. The location of this research is in the district of Tayan Hilir,region of Sanggau. The Subjects are the Government of the region of Sanggau itself which is relating to theimplementation of the revitalization policy of posyandu and also the local communities as the target of thepolicy. The conclusion of this research is that this unmaximum of the policy implementation due to severalfactors as what is stated by Edward III. Therefore, the recommendation of this policy is by re-controlling towardthe activity that related to the implementation of the revitalization policy of posyandu so that it can works wellas it aims to be.keywords: Implementation, Revitalization Polic